Modelling drivers of millennials' green consumption behaviour: an interpretive structural modelling approach. (26th June 2022) - Gupta, Anu; Verma, Hemraj; Jain, Vijay Kumar; Kumar, Pankaj
Green consumption has occupied an important role due to the growing scarcity of natural resources and the rise in global temperatures. Increasing population and income of consumers, and wealth in the coming years are likely to put pressure on the resources. The solution to the above problem lies in the adoption of environmentally friendly products and sustainable consumption. The current study aims to identify and prioritise the enablers of green consumption behaviour among millennials. The interpretive structural modelling approach has been used to prioritise the enablers of green consumptions. A total of 13 enablers were identified based on literature and experts' opinion on green consumption. Green product experience, customer pressure, and information utility were found to be the most important enablers of green consumption behaviour. The finding of the study would help policymakers and marketers to encourage green consumption among millennials, thereby, improving the environment, cutting down emissions and environmental degradation.